Vitamin-D-deficiency rickets even with abundant sunlight - a case to highlight emerging problem - Ting, Tzer Hwu; Devnani, Anand Sobhraj (Malaysian Medical Association, 2016)
We describe a case of vitamin-D-deficiency rickets in a young child to highlight its existence in Malaysia where sunlight is abundant throughout the year. The child presented with deformity of both legs. He came from an educated urban family but remained indoors most of the time. Radiographs of knees and wrists showed changes of florid rickets. Low serum 25-hydoxyvitamin-D, high parathyroid hormone, normal serum phosphate and calcium levels, and normal renal function clinched the diagnosis of vitamin-D-deficiency rickets. He improved remarkably after treatment with oral Vitamin-D. We emphasise the importance of exposure to sunlight to prevent rickets.